Experimental determination of the light-trapping-induced absorption enhancement factor in DSSC photoanodes - Gagliardi, Serena; Falconieri, Mauro (Beilstein Journal of Nanotechnology, 2015)
For dye-sensitized solar cells (DSSC), the fundamental process that determines the maximum short-circuit current is the absorption of light. In such devices, this is produced by the concurrent phenomena of light absorption by dye molecules and light trapping in the mesoporous, titania photoanode structure. The decoupling of these two phenomena is important for device characterization and the design of novel photoelectrode geometries with increased optical performance. In this paper, this task is addressed by introducing a spectral absorption enhancement factor as a parameter to quantify the light trapping effect. The experimental value of this parameter was obtained by comparing the experimentally determined fraction of absorbed light by a dye-sensitized photoanode with the light absorbed by the dye without the mesoporous titania structure. In order to gain more insight from this result, the fraction of light absorbed in the photoanode (on the basis of the dye loading capacity of the titania nanospheres) was also calculated by an optical model for the two extreme cases of the absence of light trapping and maximum light trapping. Accordingly, the photocurrent was calculated under the assumption of solar irradiation, which defined two useful boundaries. Using the experimentally derived values of the spectral absorption enhancement factor in the photoanode optical model, the DSSC short-circuit current can be calculated with good agreement with the value measured in practical devices based on the same photoanode structures. Therefore, our approach provides a realistic description of a practical device and can be exploited as an useful tool to assess the optical functionality of novel photoanode structures.
Keywords: dye-sensitized solar cells; light trapping; optical characterization; photoanode modeling; titania nanostructures